USP35 regulates mitotic progression by modulating the stability of Aurora B - Jinyoung Park (Nature Portfolio, 2018)
Aurora B kinase is a member of the chromosomal passenger complex, which is an indispensable regulator of mitosis. Here the authors show that the deubiquitinating enzyme USP35 has a role in mitotic progression by inhibiting proteasomal degradation of Aurora B kinase, leading to its activation.